Current state of implementation of certain areas of state anti-corruption policy in the sphere of public service in Ukraine - Tatiana Kovalova (Theory and Practice of Public Administration, 2019)
The article analyzes the state of implementation of the state anti-corruption policy in certain spheres of public service as of the end of 2018 and the formulation of proposals for improving its effectiveness. Emphasis is placed on electronic filing and verification of declarations made by the National Anti-Corruption Agency.In October 2014, the Verkhovna Rada of Ukraine simultaneously passes five anti-corruption laws, drafted by the Cabinet of Ministers of Ukraine. These laws created the legal and institutional foundations for a new anti-corruption policy of the state. In particular, in Art.  1 of the Law of Ukraine “On Prevention of Corruption” defines a new system of specially authorized entities in the field of combating corruption: prosecuting authorities, National Police, National Anti-Corruption Bureau of Ukraine, National Anti-Corruption Agency (NACA).The dynamics of corruption in Ukraine since the beginning of anti-corruption reform (from 2014) is as follows: in 2018, Ukraine ranked 122nd in 2018, in 2017 - 130th out of 180, 2016 - 131st from 176 countries, in 2015 - 130 out of 168 countries, in 2014 - 142 out of 175 countries [16]. According to these data, we can conclude that the level of corruption in Ukraine has slowed down. In 2018 alone, Ukraine is among the countries trying to fight corruption, scoring 32 pointsOne of the means of preventing corruption identified in the Anti-Corruption Strategy for 2014-2017 is to create a virtuous public service in accordance with international standards and best international experience. In line with the provisions of the Strategy, such tools as online filing should have been facilitated; maintaining an open, single electronic database of declarations; establishment of an independent body with sufficient powers to monitor compliance with the law on the prevention of conflicts of interest and on the completeness and certainty of declarations; the application of proportionate and dissuasive penalties for breaches of law to prevent conflicts of interest and to declare income, expenses and financial obligations. All this was introduced, but statistics show that NAPC did not fully exercise its powers. The reason for this is the lack of NACА audit staff and the lack of a software module for automatic declaration verification.The deadline for adopting the 2014-2017 Anti-Corruption Strategy has ended and no new strategy has been adopted. It is therefore advisable to recommend the NAPA: first, to plan research on measuring and evaluating corruption by selected methods, as well as the state of implementation of anti-corruption strategies; second, to prepare an analytical review of studies (regional, sectoral, etc.) conducted in Ukraine, and based on the conclusions drawn - the National Report and Anti-Corruption Strategy for the next period.